How to Organize Sustainable Individual Travels? - Pavić, Lazar; Cvahte Ojsteršek, Tina (Interdisciplinary and Applied Konwledge for Green and Digital Logistics Processes, 2026)
Tourists' activities are often marked by unsustainable behavior or a lack of awareness of the environmental, societal and economic impact of travel. Because of this, the chapter presents factors influencing travel decisions and ways to make travel and mobility within them more sustainable. It focuses on trip organization and the influence of motivation and decision-making on it. Travel motivation is explored through four groups of motives: physical, cultural, interpersonal, and status. The selection of a destination, which is determined by various factors, is also examined, emphasizing the importance of understanding this process. Mobility in tourism has a significant impact on the environment, with air travel being the most burdensome. Different forms of transportation have different environmental impacts, which is crucial for sustainable travel. When individually organizing trips, considering destination choice, mode of transportation, weather conditions, duration of travel, accommodation, finances, and the reality of destination information is recommended. Mobility at the destination is crucial as tourist visits can burden the environment. Sustainable transportation modes such as walking, cycling, and public transport are recommended to reduce environmental impacts and enable more authentic tourist experiences.